Coffee story: Unveiling indigenous delicacy through sensorial transaction - Fariz Hirzan; Yandi Andri Yatmo (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
This paper explores the potential of spatial atmosphere as the basis of a coffee stall design, creating an intimate understanding of the possible sensory transactions that occurred throughout the coffee-brewing process. In this reflective piece, a coffee stall design process is presented and dissected to unveil the programmatic basis of the design. A closer look at multi-sensory experiences that include sight, smell, and sound in the process of brewing is considered essential. They hold a significant role in perceiving the surrounding atmosphere and how it impacts our design process. A series of equipment and ingredient tracing is conducted to identify the optimal barista's workflow and the production of a multi-sensory experience, rethinking the purpose of the surrounding objects from two different perspectives. Such a process positioned the atmosphere exploration as a focus in achieving a unique programme where the objects within the coffee-making process generate the space through materiality and immateriality.